A Rare Case of Perforated Descending Colon Cancer Complicated with a Fistula and Abscess of Left Iliopsoas and Ipsilateral Obturator Muscle. (16th March 2014) - Cacurri, Alban; Cannata, Gaspare; Trastulli, Stefano; Desiderio, Jacopo; Mangia, Antongiulio; Adamenko, Olga; Pressi, Eleonora; Giovannelli, Giorgio; Noya, Giuseppe; Parisi, Amilcare
Abstract : Perforation of descending colon cancer combined with iliopsoas abscess and fistula formation is a rare condition and has been reported few times. A 67-year-old man came to our first aid for an acute pain in the left iliac fossa, in the flank, and in the ipsilateral thigh. Ultrasonography and computed tomography revealed a left abdominal wall, retroperitoneal, and iliopsoas abscess that also involved the ipsilateral obturator muscle. It proceeded with an exploratory laparotomy that showed a tumor of the descending colon adhered and perforated in the retroperitoneum with abscess of the iliopsoas muscle on the left-hand side, with presence of a fistula and liver metastases. A left hemicolectomy with drainage of the broad abscess was performed. Pathologic report findings determined adenocarcinoma of the resected colon.